An Analysis of Confidence In Speaking Skill of Grade VIII Student At Mts Ddi Siapo - Astrian Yulianti; Jaya; Darwin (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
This study aims to identify and discribe the self-confidence and speaking skills of eighth-grade students at MTs DDI Siapo. Speaking is a fundamental skill in English learning that is influenced not only by linguistic factors but also by psychological factors such as self-confidence. This study used a qualitative descriptive method through semi-structured interviews with nine students. The results showed that most students had low self-confidence, characterized by nervousness, shyness, fear of making mistakes, and negative assessments of their speaking abilities. These psychological barriers significantly impacted students' willingness to speak English. This study identified five main indicators affecting student self-confidence: perception of self-ability, previous success experiences, social support, response to mistakes or social judgment, and personal motivation and determination. Students with high self-confidence tended to be more active and confident in speaking, while students with low self-confidence were more passive and reluctant to participate.